A Sociolinguistics Analysis of Language Style in Vaughn's The King's Man: Sociolinguistic Landscape, Language Styles, Social Factors, Cinematic Narratives, The King’s Man - Doaly, Christa Putri; Posumah, Jenie; Tuilan, Jeane (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study investigates the sociolinguistic landscape of “The King’s Man,” a World War I spy action film, using Martin Joos’ five-point framework and Janet Holmes’ concept of social factors. It uncovers a variety of language styles, each tailored to the characters’ social context and communicative objectives. These include the solemn and authoritative frozen style (3 instances), the deliberative style for conveying instructions and asserting authority (24 instances), the consultative style in advice and justification exchanges (20 instances), the casual style in informal conversations (12 instances), and the intimate style in emotionally charged moments (5 instances). The study emphasizes the significant role of social factors in language choices, with characters using language to navigate social hierarchies, express emotions, and influence events. It highlights the complex interplay between language and social contexts in the film, offering deeper insight into characters’ inner worlds, social dynamics, and the film’s impact on the audience, ultimately revealing the interconnectedness of language, society, and storytelling in cinema.